2014
DOI: 10.1039/c3sm52631c
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembly of chiral tubules

Abstract: The efficient and controlled assembly of complex structures from macromolecular building blocks is a critical open question in both biological systems and nanoscience. Using molecular dynamics simulations we study the self-assembly of tubular structures from model macromolecular monomers with multiple binding sites on their surfaces [Cheng et al., Soft Matter, 2012, 8, 5666-5678]. In this work we add chirality to the model monomer and a lock-and-key interaction. The self-assembly of free monomers into tubules … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 29 publications
0
22
0
Order By: Relevance
“…Tubular structures such as microtubules 31 or the Tobacco Mosaic Virus 32 are commonly found in nature. Self-assembly into chiral tubular structures has been suggested to be driven by a balance of both lateral and longitudinal contacts at the monomer level 33 . An in-depth understanding of the specific intermolecular forces that drive the self-assembly of tubular self-assemblies will provide insight into the molecular design of supramolecular nanotubes.…”
mentioning
confidence: 99%
“…Tubular structures such as microtubules 31 or the Tobacco Mosaic Virus 32 are commonly found in nature. Self-assembly into chiral tubular structures has been suggested to be driven by a balance of both lateral and longitudinal contacts at the monomer level 33 . An in-depth understanding of the specific intermolecular forces that drive the self-assembly of tubular self-assemblies will provide insight into the molecular design of supramolecular nanotubes.…”
mentioning
confidence: 99%
“…They consist of tubular polymers of tubulin proteins. Focusing on the self‐assembly of tubular structures with multiple binding sites, Cheng et al studied the fundamentals of microtubule assembly (Figure (g)). They developed a CG model monomer that is able to self‐assemble into tubular structures and may serve as a model for microtubule studies.…”
Section: Structural Investigation On Ppismentioning
confidence: 99%
“…For example, molecular dynamics (MD) simulations using a wedge‐shaped monomer (Fig. a) have recently demonstrated that self‐assembly into tubule structures depends on key factors such as molecular orientation and the relative influences of both lateral (transverse to the tube) and vertical (along the tube length) molecular interaction strengths (Cheng et al, ; Cheng and Stevens ). MD has further shown that the pitch of the tubule can be controlled by the chirality of the monomer, but also that a twist deformation tends to yield a range of pitch values.…”
Section: Toward Artificial Microtubule Filamentsmentioning
confidence: 99%